New species of sabellariids (Annelida: Sabellariidae) from the Caribbean Sea and the Gulf of Mexico - Chávez-López, Yessica (European Journal of Taxonomy, 2022)
In the Caribbean Sea and the Gulf of Mexico, 15 species of sabellariids have been described. Since Kirtley’s (1994) worldwide review, at least seven species have not been re-recorded for this region. Therefore, the aims of this contribution were: a) to review the sabellariids held in scientific collections, b) to generate standardized descriptions, and c) to provide taxonomic identification keys for the species of the region. The sabellariids of two Mexican and one US scientific collection were reviewed. Five new species are described: Lygdamis pechi sp. nov. from Veracruz, Gulf of Mexico, Mariansabellaria caribbea sp. nov. from Quintana Roo, Mexico, Phalacrostemma danieli sp. nov. from southwest of Grenada, Tetreres israeli sp. nov. from the Virgin Islands, and T. oscari sp. nov. from Florida. Another morphospecies, Phalacrostemma sp., is characterized by a single incomplete specimen from the Bahamas. Also, new records of Phalacrostemma perkinsi Kirtley, 1994, and P. dorothyae Kirtley, 1994 were made.